2018
DOI: 10.1021/acs.jctc.8b00781
|View full text |Cite
|
Sign up to set email alerts
|

Universal Method for Electrostatic Interaction Energies Estimation with Charge Penetration and Easily Attainable Point Charges

Abstract: Our new model of electron density augmented by point charges (aug-PROmol) provides an estimation of electrostatic interaction energies including penetration effects (ChemPhysChem 2016, 17, 2455–2460). In this paper we prove that it can be applied using sources of point charges other than those from direct restrained fitting to electrostatic potential (RESP). We used a newly established databank of tabulated invariom point charges and a widely known semiempirical method. Both sources perform equivalently to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…As an ultimate reference we used quantum mechanics values obtained at the DFT-SAPT/B3LYP/aug-cc-pVTZ level (Bojarowski et al, 2018). To validate if new models are better in the electrostatic energy estimation than already known models we used the results obtained from tailored UBDB approach (simultaneous refinement of all multipole model parameters) computed at the B3LYP/6-31G** as described in the 2.1.1 section, and from the aug-PROmol approach taken from our previous publications (Bojarowski et al, 2016;2018).…”
Section: Reference Values Of Electrostatic Energymentioning
confidence: 99%
See 2 more Smart Citations
“…As an ultimate reference we used quantum mechanics values obtained at the DFT-SAPT/B3LYP/aug-cc-pVTZ level (Bojarowski et al, 2018). To validate if new models are better in the electrostatic energy estimation than already known models we used the results obtained from tailored UBDB approach (simultaneous refinement of all multipole model parameters) computed at the B3LYP/6-31G** as described in the 2.1.1 section, and from the aug-PROmol approach taken from our previous publications (Bojarowski et al, 2016;2018).…”
Section: Reference Values Of Electrostatic Energymentioning
confidence: 99%
“…The Pv𝜅 model is significantly worse only for short distances in electrostatic dimers. Knowing the construction of the aug-PROmol model (Bojarowski et al, 2018), it can be concluded that expansion-contraction parameters are very important and their fine tuning may lead in the future to even better results.…”
Section: Electrostatic Energy Estimations From New Electron Density Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unable to take into account such phenomena as electron polarization, subtle details of electron density anisotropy, and charge penetration. Considerable efforts have been devoted to provide a more realistic description of intermolecular interactions by including the aforementioned aspects with recent emphasis on penetration energy (Epen) [15][16][17][18][19][20][21][22][23][24][25]. Here we based our analysis on the University at Buffalo Databank (UBDB) of transferable atomic densities [26][27][28], from which the charge densities of protease-inhibitor complexes was reconstructed.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been devoted to provide a more realistic description of intermolecular interactions by including the aforementioned aspects with recent emphasis on penetration energy (Epen). [12][13][14][15][16][17][18][19][20][21][22] The analysis is based on a data bank of transferable atomic densities [23][24][25] , from which the charge density of the protease-inhibitor complexes is reconstructed. Electrostatic interaction energies are then evaluated using an exact algorithm for the short-range interactions and the Buckingham approximation for non-overlapping densities for atoms at large distances 26 .…”
Section: Introductionmentioning
confidence: 99%